Frequency of nutritional disorders and their risk factors among children attending 13 nurseries in São Paulo, Brazil: a cross-sectional study - Konstantyner, Tulio; Taddei, José Augusto Aguiar Carrazedo; Konstantyner, Thais Cláudia Roma Oliveira; Rodrigues, Laura Cunha (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Nutritional disorders are associated with health problems earlier in life. The objective here was to estimate the frequency of nutritional disorders and their risk factors among children. DESIGN AND SETTING: Cross-sectional study in nurseries at 13 day-care centers in São Paulo, Brazil. METHODS: The mothers of 482 children were interviewed, with anthropometry on these children. Chil-dren whose anthropometric indices for weight and height were greater than two standard deviations were considered to have nutritional disorders. RESULTS: Children in families with lower per capita income (odds ratio [OR]: 2.25; 95% confidence interval, CI: 1.08-4.67) and who presented neonatal risk (OR 8.08; 95% CI: 2.29-28.74), had incomplete vaccinations (OR 3.44; 95% CI: 1.15-10.31) or were male (OR 3.73; 95% CI: 1.63-8.56) were more likely to be malnourished. Children in families with lower per capita income were also less likely to be overnourished (OR 0.40; 95% CI: 0.19-0.88). Children who were exclusively breastfed for less than two months (OR 2.95; 95% CI: 1.35-6.44) or who were male (OR 2.18; 95% CI: 1.02-4.65) were also at greater risk of being overnourished. Children who presented neonatal risk (OR 3.41; 95% CI: 1.04-11.23), had incomplete vaccinations (OR 3.18; 95% CI: 1.30-7.76), or were male (OR 2.76; 95% CI: 1.56-4.90) were more likely to have a nutritional disorder. CONCLUSIONS: Nutritional disorders remain present in children attending nurseries in São Paulo. Actions should focus on boys, children who were exclusively breastfed for less than two months and those without up-to-date vaccinations.